Circulating Vitamin D, Vitamin D-related genetic variation, and risk of fatal prostate cancer in the National Cancer Institute Breast and Prostate Cancer Cohort Consortium - Shui, Irene M (Cancer, 2015)
BACKGROUND: Evidence from animal and cell line experimental studies support a beneficial role for vitamin D in prostate cancer (PCa). While the results from human studies have been mainly null for overall PCa risk, there may be a benefit for survival. We assessed the associations of circulating 25-hydroxyvitamin D [25(OH)D] and common variation in key vitamin D-related genes with fatal PCa. METHODS: In a large cohort consortium, we identified 518 fatal cases and 2986 controls with 25(OH)D data. Genotyping information for 91 single nucleotide polymorphisms (SNPs) in 7 vitamin D-related genes (VDR, GC, CYP27A1, CYP27B1, CYP24A1, CYP2R1, RXRA) was available for 496 fatal cases and 3577 controls. We used unconditional logistic regression to calculate odd ratios (OR) and 95% confidence intervals (CI) for the associations of 25(OH)D and SNPs with fatal PCa. We also tested for 25(OH)D-SNP interactions among 264 fatal cases and 1169 controls. RESULTS: We observed no statistically significant relationship between 25(OH)D and fatal PCa [OR(95% CI)(extreme quartiles)=0.86(0.65-1.14); p-trend=0.22] or the main effects of the SNPs and fatal PCa. There was suggestive evidence that associations of several SNPs (including 5 related to circulating 25(OH)D) with fatal PCa were modified by 25(OH)D. Individually these associations would not remain significant after considering multiple testing; however the p-value for the set-based test for CYP2R1 was 0.002. CONCLUSIONS: In our study, we did not observe statistically significant associations for either 25(OH)D or vitamin D-related SNPs with fatal PCa. Effect modification of 25(OH)D associations by biologically plausible genetic variation may deserve further exploration.